Prepregnancy body mass index, gestational weight gain, and maternal prepartum inflammation in normal pregnancies: findings from a Chinese cohort - Kuanrong Li; Chuanzi Yang; Jiaying Fan; Xiaojun Li; Chongjuan Gu; Huishu Liu (BMC Pregnancy and Childbirth, 2022)
Abstract Background Obesity has been linked to systemic inflammation in population studies. Objective To examine the associations of prepregnancy body mass index (pBMI) and total gestational weight gain (tGWG) with maternal prepartum low-grade inflammation (LGI) and clinically significant inflammation (CSI) defined by serum C-reactive protein (CRP) concentration. Methods Five thousand four hundred seventy-six Chinese women with uncomplicated pregnancies and recorded data on pBMI and prepartum body weight were included in this study. Blood samples were drawn before delivery for high-sensitivity CRP assay. Inadequate, optimal, and excessive tGWG were defined using the Institute of Medicine's recommendation. Multivariable Poisson regressions were used to estimate relative risks (RRs) for having prepartum LGI and CSI (defined as CRP concentration 3–10 and > 10 mg/L, respectively) across pBMI and tGWG categories. Results The mean pBMI, mean tGWG, and median maternal prepartum CRP concentration were 20.4 kg/m2, 13.9 kg, and 3.3 mg/L, respectively. The prevalence of prepartum CSI and LGI was 7.2% and 47.8%. The adjusted RRs (95% confidence interval) of CSI for normal (18.5–24.9 kg/m2) and high (≥ 25 kg/m2) vs. low pBMI (< 18.5 kg/m2) were 1.35 (1.05–1.74) and 2.28 (1.53–3.39), respectively. The respective adjusted RRs of LGI were 1.19 (1.11–1.28) and 1.59 (1.42–1.77). The adjusted RRs for excessive vs. optimal tGWG was 1.18 (0.94–1.48) for CSI and 1.14 (1.07–1.21) for LGI. Conclusions Prepregnancy overweight/obesity and excessive tGWG increase the risk of maternal prepartum systemic inflammation, which further highlights the importance of weight management before and during pregnancy.